The Problem with Amphotericin - Cavell, Gillian (Clinical drug investigation, 2020)
Patient harm from inadvertent administration of amphotericin B (Fungizone™) instead of liposomal amphotericin (AmBisome ® ) has been described in the literature and has been the subject of patient safety alerts in the UK. Safe use of intravenous amphotericin depends on the knowledge and awareness of practitioners of the availability and differences between the different presentations of intravenous amphotericin. Knowledge is a weak barrier to error. Recommendations to reduce the risk of error following adverse drug events in the UK, USA and The Netherlands have largely focused on actions to be taken at an organisational level, such as drug supply, storage, dose checking and specifying brand and generic names on prescriptions. None have considered or addressed the contributory factors relating to the products themselves, namely the similarity between the presentations of AmBisome and Fungizone, both of which are manufactured as 50 mg vials despite their different dose recommendations. The need to use multiple vials of Ambisome to prepare infusions for adult patients is contrary to the usual practice of using only one or two vials to prepare doses of injectable medicines for adult patients, increasing the risk of error not only with injectable amphotericin formulations but potentially also with the preparation of other injectable medicines. Whilst the development of robust local risk reduction strategies are important, external factors, such as the design of medicines, should also be identified and highlighted to manufacturers and regulatory authorities as potential contributors to error and harm.